PEMANFAATAN PERMAINAN TRADISIONAL SEBAGAI MEDIA PEMBELAJARAN ANAK USIA DINI UNTUK MENGEMBANGKAN ASPEK MORAL DAN BAHASA ANAK - Haris, Irfan (Widya Wacana: Jurnal Ilmiah, 2016)
Research "Utilization of Traditional Games as Media Learning Early Childhood to DevelopAspects of Moral and Language Children" has the purpose of knowing the type of traditionalgames that can be developed as a learning medium, and examine the use of traditional gameseffectively used as a medium of learning can develop moral aspects and language olds early.The method used in this research is the Research and Develoment because researchers want todevelop traditional games as Jamuran Games and sluku-sluku bathok Games to develop moraland languages (Arabic, English, Javanese and Indonesian) early childhood. The development oflearning tools compiled in this study refers to the type of development model 4-D (four D model),which consists of four stages. The fourth stage is the stage of definition (define), stage design(design), the development stage (development), and the deployment phase (disseminate).Results of this research is Jamuran Games and sluku-sluku bathok Games as effective learningmedia can develop moral and linguistic aspects of early childhood with a percentage of 80% oflearners who pass the study.Keywords: Traditional Games, Media Education, Early Childhood